Analisis Kelayakan Usaha Produksi Susu Kambing Peranakan Etawa (PE) Di Tharraya Farm Di Desa Geli Kecamatan Sunggal Kabupaten Deli Serdang - Susi Susanti. L. Gultom; Dedek Putri; Ernawati Ernawati; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Research on Feasibility Analysis of the Etawa Peranakan Goat Milk Production Business (PE) at Tharraya Farm in Geli Village, Sunggal District, Deli Serdang Regency aims to analyze the income of the goat milk (PE) production business at Tharraya Farm and analyze the feasibility of the goat milk production business (PE) in Tharraya Farm. The research area was determined purposively, namely based on certain criteria or objectives, taking into account that the Etawa goat milk industry in the area could provide the information needed in the research. Data analysis techniques used were I=TR-TC. The results of this research obtained an income of IDR 72,240,000 / year. Receipts amounting to Rp. 176,526,000 a year and total costs of 104,286,000. The livestock business is profitable and feasible to develop with an R/C of 1.69, п>0, while the percentage ratio of п/C x 100% is 60%. The Etawa Peranakan goat milk business at Therraya Farm is profitable and worthy of development